A ESCRITA DOS JOVENS E ADULTOS DA EJA DA ESCOLA PADRE CHAGAS, EM SANTA INÊS MARANHÃO: a possibilidade de organização do texto pela noção de gênero textual - Quaresma, Elinaldo (2011)
This dissertation aims at the analyses of writing practices that take place using diverse text genre by EJA (Educação de Jovens e Adultos) students of Padre Chagas State School, in Santa Ines, Maranhão. Assuming these students conceptions of writing production are constructions from their own community historic and cultural background mediated by language, this dissertation researches this group of students writing production for the meanings given to the text and their construction process. In order to do that, this study seeks theoretical foundation on the conception that is through the text that the language user develops one s ability to organize thought and knowledge and to transfer ideas, information and opinions in multiple communicative situations. This research has contributions from Bagno, Marcuschi , Bakhtin, Dionísio, and so on. Beside thoses, there are also other authors who specifically approach the historical process of EJA as part of an educational policy: Freire, Paiva, Galvão and Soares and others. The socio-cultural perspective guided the research procedures and the developed analyses of the empirical material produced during interviews and classroom practices. The subjects were the main teacher and her thirty EJA high school students from Padre Chagas State School. The adopted procedure to collect data was the use of questionnaires, interviews and writing production samples from the classes in order to have maximum information about the object of the research, which involves students writing production. From this analysis it was possible to notice the great number of difficulties students face when producing a written text or recognizing a certain text genre. Although there is an attempt of an innovative pedagogical focus through the text genre, what prevails is the developing the concept that a text is a result of historical and cultural environment, and so it must be treated in class.